HCl and O2 co-activated bis(8-quinolinolato) oxovanadium(iv) complexes as efficient photoactive species for visible light-driven oxidation of cyclohexane to KA oil. Issue 2 (25th October 2018) - She, Jialuo; Lin, Xiangfeng; Fu, Zaihui; Li, Jianwei; Tang, Senpei; Lei, Ming; Zhang, Xin; Zhang, Chao; Yin, Dulin
Abstract : Photoactive species (PA) originating from HCl and O2 co-activated bis(8-quinolinolato) oxovanadium(iv ) can effectively modulate the photocatalytic oxidation of cyclohexane. Abstract : This paper reports three bis(8-quinolinolato) oxovanadium(iv ) complexes that are active for visible light-induced cyclohexane oxygenation under O2 (1 atm) in acetonitrile with HCl participation, achieving greater than 18% conversion and 86% selectivity for KA oil (cyclohexanone and cyclohexanol), along with a small amount of chlorinated product. Notably, these V IV OQ2 complexes are not only basically comparable to V IV O(acac)2 and some typical V V -compounds in photocatalytic activity but are also more selective for KA oil. Spectral characterizations (XPS, FT-IR and UV-vis) and DFT calculations support that V IV OQ2 complexes can be co-activated by HCl and O2 to form the V V O(OH)-containing photoactive (PA) species with one pendant ligand's phenoxyl radical and an axially coordinated chlorine, which are responsible for the present photocatalytic oxidation. Noteworthily, increasing the Cl-substituents of V IV OQ2 complexes and especially the amount of water in the reaction system obviously decelerated the generation of such PA species, which significantly improved the selectivity for KA oil.